Emotional dysregulation and its pathways to suicidality in a community-based sample of adolescents - Mittermeier, Sabrina; Seidel, Alexandra; Scheiner, Christin; Kleindienst, Nikolaus; Romanos, Marcel; Buerger, Arne (Child and adolescent psychiatry and mental health, 2024)
Effective suicide prevention for adolescents is urgently needed but difficult, as suicide models lack a focus on age-specific influencing factors such as emotional dysregulation. Moreover, examined predictors often do not specifically consider the contribution to the severity of suicidality. To determine which adolescents are at high risk of more severe suicidality, we examined the association between emotional dysregulation and severity of suicidality directly as well as indirectly via depressiveness and nonsuicidal self-injury. Adolescents from 18 high schools in Bavaria were included in this cross-sectional and questionnaire-based study as part of a larger prevention study. Data were collected between November 2021 and March 2022 and were analyzed from January 2023 to April 2023. Students in the 6th or 7th grade of high school (11-14 years) were eligible to participate. A total of 2350 adolescents were surveyed and data from 2117 students were used for the analyses after excluding incomplete data sets. Our main outcome variable was severity of suicidality (Paykel Suicide Scale, PSS). Additionally, we assessed emotional dysregulation (Difficulties in Emotion Regulation Scale, DERS-SF), depressiveness (Patient Health Questionnaire, PHQ-9) and nonsuicidal self-injury (Deliberate Self-Harm Inventory, DSHI). In total, 2117 adolescents (51.6% female; mean age, 12.31 years [standard deviation: 0.67]) were included in the structural equation model (SEM). Due to a clear gender-specific influence, the model was calculated separately for male and female adolescents. For male adolescents, there was a significant indirect association between emotional dysregulation and severity of suicidality, mediated by depressiveness (β = 0.15, SE = .03, p = .008). For female adolescents, there was a significant direct path from emotional dysregulation to severity of suicidality and also indirect paths via depressiveness (β = 0.12, SE = .05, p = 0.02) and NSSI (β = 0.18, SE = .04, p < .001). Our results suggest that gender-related risk markers in 11-14-year-olds need to be included in future suicide models to increase their predictive power. According to our findings, early detection and prevention interventions based on emotion regulation skills might be enhanced by including gender-specific adjustments for the co-occurrence of emotional dysregulation, depressiveness, and nonsuicidal self-injury in girls and the co-occurrence of emotional dysregulation and depressiveness in boys.
Gesehen am 04.03.2025